Persepsi Narendra Modi Dalam Kebijakan India Menarik Diri Dari Regional Comprehensive Economic Partnership Tahun 2019 - Azhari, Azhari; Darman Moenir, Haiyyu; Jamillah, Maryam (Hubungan Internasional Universitas Andalas, 2022)
The Prime Minister of India, Narendra Modi introduced the Act East Policy (AEP) which was presented at the ASEAN Summit in Myanmar, November 2014. The AEP policy is a reflection of the long-term economy and takes advantage of its strategic position to create closer relations with countries in the Asian region. Pacific. One of the ways to achieve India's economic growth is to establish various frameworks of economic cooperation. However, in the Regional Comprehensive Economic Partnership (RCEP) agreement in the negotiation stage, Modi withdrawal India from RCEP. This research aims to analyze The perception of Modi in formulating India policy of withdraw from the 2019 RCEP. This research has its urgency because India's political dynamics have initially participated in negotiations since 2012 during Modi's leadership period, then decided to withdraw from the RCEP.. This shows that Narendra Modi has his own perception of RCEP. To see Modi's perception, this research uses a framework of thinking about the relationship between perception and decision making according to Ole R. Holsti. This study uses a qualitative research method with a descriptive analytical approach using secondary data. Furthermore, based on a framework related to Holsti's perception, this study finds that Modi's belief system and image are not in line with RCEP because it is not in accordance with the belief system that influenced Modi, namely the rejection of domestic actors, the trade balance deficit, the rejection of the Three Tier Approach proposal, Hindu nationalist and Gandhiji Talisman and not in accordance with the image that should have happened according to Modi, namely realizing Make in India and India First.